Minat Belajar dan Kemampuan Baca Al-Qur’an Anak Nelayan - Hafizah Tulwardiah; Ulfatmi Ulfatmi; Muhammad Zalnur (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2024)
This research is motivated by the interest in learning to learn to read the Qur'an is very important for santri / female students of fishermen's children at MDTA Darul Hujjaj Joundul II Complex Tabing Hajj Dormitory. The purpose of this research in general is to find out how the interest in learning and the ability to read the Qur'an of fishermen's children at MDTA Darul Hujjaj Joundul II Complex Tabing Hajj Dormitory. This research uses a qualitative approach in the form of a case study. Data collection techniques in this study are using observation, interview and documentation techniques. Then the data that has been collected is processed with the analysis model. The results of the research conducted, the author can conclude that there are several variations in the interest and ability to read the al quran of fishermen's children at MDTA Darul Hujjaj. For santri who have been able to read Al quran and Iqro‘ fluently on average have a high interest in learning Al qur'an, while on the contrary for santri who have not been able to read Al quran and Iqro’ on average have a low interest in learning Al qur'an. Therefore, the figure of a teacher in this process is an important thing, because from the results of the study it is concluded that the way and method of teaching an MDTA teacher can affect the ability and interest in reading of fishermen's children in MDTA Darul Hujjaj.